Involvement of shared resources in time judgment and sequence reasoning tasks - Brown, Scott W. (Acta psychologica, 2014)
Previous research suggests that time perception is supported by the same attentional resources involved in sequence processing. The present experiment was designed to clarify this connection by examining the relation between timing and reasoning tasks that involved either sequencing or non-sequencing judgments. For the timing task, subjects produced a series of 5-s intervals. For the reasoning tasks, subjects judged whether pairs of statements describing common actions either (a) were presented in the correct temporal order (sequencing), or (b) described similar actions or objects (similarity). Subjects performed the timing and reasoning tasks both separately and concurrently in a series of 3-minute trials. Comparisons of single-task and dual-task performance assessed interference patterns between concurrent tasks. Both reasoning tasks interfered with timing by making temporal productions longer and more variable. Timing had differential effects on the two reasoning tasks. Concurrent timing caused sequencing judgments to become slower, less accurate, and less sensitive relative to sequencing-only conditions. In contrast, similarity judgments were either unaffected or affected to a lesser degree by the concurrent timing task. These results support the notion that timing and sequencing are closely related processes that rely on the same set of cognitive resources or mechanisms. •Timing and reasoning tasks were performed under single- and dual-task conditions.•The reasoning tasks involved judgments about sequencing or similarity.•Both reasoning tasks interfered with time judgments.•Timing interfered with sequencing judgments, but not with similarity judgments.•Timing and sequencing appear to rely on common attentional resources.